Active surveillance for adult low-risk papillary thyroid microcarcinoma—a review focused on the 30-year experience of Kuma Hospital— - Yasuhiro Ito; Akira Miyauchi; Makoto Fujishima; Masashi Yamamoto; Takahiro Sasaki (Endocrine Journal)
Active surveillance (AS) for low-risk papillary thyroid microcarcinoma (PTMC), which was initiated at Kuma Hospital (Kobe, Japan) in 1993 and Cancer Institute Hospital (Tokyo) in 1995, is now gradually being adopted worldwide, and several prospective studies have described the favorable outcomes of PTMC patients who underwent AS. The most important factor predicting PTMC growth is young age, and PTMC enlargement in young patients may be affected by high serum levels of thyroid-stimulating hormone. This review notes that one patient showed lung metastasis after conversion surgery (CS) following AS, but there are no reports of patients dying of thyroid carcinoma during or after AS. Some PTMCs enlarge or show newly appeared metastatic nodes requiring CS, and findings on the postoperative prognosis and incidence of significant surgical complications (e.g., permanent vocal cord paralysis, hypoparathyroidism) do not differ significantly between patients who underwent CS after AS and those who underwent immediate surgery (IS). IS has been associated with significantly higher incidences of these complications compared to AS as the initial management. Several studies have examined the quality of life (QoL) of patients who underwent AS versus IS, and reported discrepant findings regarding various psychological conditions (including anxiety). Medical costs for AS and IS vary regionally, and in Japan, the 10-year total cost of IS was 4.1 times greater than that of AS in 2017. Taken together, the existing findings demonstrate that AS can be appropriate for the initial management of patients with PTMC.